Does the Contract Matter? Regulating Business Advise Services between Advisor and Small Family Business - Katarzyna LOBACZ (Communications of International Proceedings, 2021)
Business advise is considered to be one of the sources of knowledge for small businesses. Family businesses are known as firms based to a large extent on family relationships, that potentially affect their higher propensity to use trust-based relationships inside and outside the company. The paper focuses on the extent to which trust or written contracts are used in contracting business advice services for small family businesses. The analysis is based on results of a study of 400 micro and small companies operating in Poland, who had used the external business advice. The results indicate a significant role for trust as the control form in the advisory contracts, while also a high proportion of formal relationships has been identified. It is also evidenced that the propensity to formalize the control of advisory contracts increases with the level of management complexity, however this seems to be slightly modified by existence of family relations within the small firm.
Keywords: Small Family Firm; Contract; Business Advice; Trust.